1999
DOI: 10.1002/(sici)1099-1085(19990615)13:8<1277::aid-hyp765>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate change on sea water intrusion in coastal aquifers

Abstract: There is increasing debate these days on climate change and its possible consequences. Much of this debate has focused in the context of surface water systems. In many arid areas of the world, rainfall is scarce and so is surface runoff. These areas rely heavily on groundwater. The consequences of climate change on groundwater are long term and can be far reaching. One of the more apparent consequences is the increased migration of salt water inland in coastal aquifers. Using two coastal aquifers, one in Egypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 1 publication
3
64
0
Order By: Relevance
“…Hull and Titus (1986) , Sherif and Singh (1999) , Essink (1996Essink ( , 2001aEssink ( , 2001b , Hay and Mimura (2005) , Ranjan et al (2006) Titus et al (1987) and generally exacerbate them. For instance, coastal erosion will tend to degrade or remove natural protective features (e.g.…”
Section: Freshwater Injection [P] Change Water Abstraction [A/r]mentioning
confidence: 99%
“…Hull and Titus (1986) , Sherif and Singh (1999) , Essink (1996Essink ( , 2001aEssink ( , 2001b , Hay and Mimura (2005) , Ranjan et al (2006) Titus et al (1987) and generally exacerbate them. For instance, coastal erosion will tend to degrade or remove natural protective features (e.g.…”
Section: Freshwater Injection [P] Change Water Abstraction [A/r]mentioning
confidence: 99%
“…Saline groundwater occurs underground in unconfined coastal aquifers at a depth ( z ) below sea level of about 40 times the height ( h f ) of the fresh water above sea level: z = 40 h f (Todd & Mays, ). According to Sherif and Singh (), when the level of the Mediterranean Sea rises by 0.5 m, seawater intrusion will influence areas up to 9 km from the coast. Moreover, Werner and Simmons () demonstrated that seawater can intrude up to 5 km from coastal areas through seawater‐intrusion boundary simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is a topic of huge interest for scientists, stakeholders and the public, due to its long‐term direct impacts and consequences. Many researchers reported increasing temperatures for the 20 th Century (Sherif and Singh, ; Shaver et al ., ; IPCC, ; Dong et al ., ; Xie et al ., ) and an increase from 1 to 3 °C is predicted for the 21 st century (Stavig et al ., ; IPCC, ). The ongoing global warming (Haeberli et al ., ; Kargel et al ., ) is triggering global consequences and it is likely also to alter natural systems at the local scale.…”
Section: Introductionmentioning
confidence: 99%